PENGARUH RISIKO AUDIT TERHADAP BIAYA AUDIT EKSTERNAL DI INDONESIA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Tahun 2018-2019) - Gracea Allesandra Vinidita; Imam Ghozali (Diponegoro Journal of Accounting, 2021)
The aim of this study is to look into the impact of audit risk on the audit fees calculation. In this study, the independent variables are inherent risk, control risk, and detection risk, while the dependent variable is audit fees. Audit quality and firm size were also used as control variables in this study. This study uses quantitative methods. The sample in this study consists of all manufacturing firm in Indonesia Stock Exchange for the period 2018 to 2019. Total sample determined in this research is 87 companies based on purposive sampling. This study used multiple linear regression analysis for hypotheses testing. The results of this study indicate that not all attributes of audit risk such as inherent risk, control risk, and detection risk have a significant effect on the determination of audit fees in Indonesia..